Fast and Simple Preparation of a Sensor Based on Electrochemically Reduced Graphene Oxide (rGO) for the Determination of Zopiclone in Pharmaceutical Dosage by Square Wave Adsorptive Stripping Voltammetry (SWAdSV). Issue 4 (16th November 2022) - Navarro, Freddy; Segura, Rodrigo; Godoy, Fernando; Martí, Angel A.; Mascayano, Carolina; Aguirre, Maria J.; Flores, Erick; Pizarro, Jaime
Abstract: The interactions of zopiclone with electrochemically reduced graphene oxide (rGO) modified electrode were examined. A comparison of GC/rGO and glassy carbon electrode (GC) by electrochemical impedance spectroscopy and scanning electrochemical microscopy (SECM) shows that the modified surface is much less conductive than GC. The role of rGO is to act as a site of specific adsorption of the analyte. Molecular dynamics showed that the monoanionic form of zopiclone presents more interactions with defects of rGO. The analytical methodology allowed obtaining a linearity of 10–130 μg L −1, with a limit of detection of 2.14 μg L −1 using SWAdSV at pH 10.0. Abstract :